Predicted slowdown in the rate of Atlantic sea ice loss. Issue 24 (19th December 2015) - Yeager, Stephen G.; Karspeck, Alicia R.; Danabasoglu, Gokhan
Abstract: Coupled climate models initialized from historical climate states and subject to anthropogenic forcings can produce skillful decadal predictions of sea surface temperature change in the subpolar North Atlantic. The skill derives largely from initialization, which improves the representation of slow changes in ocean circulation and associated poleward heat transport. We show that skillful predictions of decadal trends in Arctic winter sea ice extent are also possible, particularly in the Atlantic sector. External radiative forcing contributes to the skill of retrospective decadal sea ice predictions, but the spatial and temporal accuracy is greatly enhanced by the more realistic representation of ocean heat transport anomalies afforded by initialization. Recent forecasts indicate that a spin‐down of the thermohaline circulation that began near the turn of the century will continue, and this will result in near‐neutral decadal trends in Atlantic winter sea ice extent in the coming years, with decadal growth in select regions. Key Points: Ocean thermohaline circulation variations drove recent decadal Arctic winter sea ice trends Initialized climate model ensembles can skillfully predict Arctic winter sea ice trends Decadal trends in Atlantic winter sea ice will be neutral or positive in the near future